The Strategic Path Ways to Improves the Performance of Scopus Indexed Journal Publication - Budi Mulyono, K; Saki, W; Nuryana, I (KnE Social Sciences, 2018)
The aim and orisinality of this study is exploring new causal pathways to develop an established research model to see the determinations of factors that determine the performance of lecturers in publishing into scoopus indexed journal. The unit of analysis in this research is all UNNES Lecturers spread in 8 faculties and post graduate program. The method of data collection in this study is a closed questionnaire with a scale of 1-7 agree-disagree intervals. Data analysis techniques in this study consisted of (1) descriptive analysis, through percentage descriptions of each variable, (2) as well as inferential analysis. The results in this study indicate that the need for affiliation, need for achievement, need for power has no effect on publication performance directly, but they impact on the publicarion performance trough work intention. The conclusions and suggestions of this research are to increase the publication necessary for the leadership to stimulate an increasing need for achievement and affiliation through the support of both policy and funding at the study centers in each unit. Keywords: need for achivement, need for affiliation, need for power, work intention, performance of lecturer in publications.